24-Month Clinical, Immuno-Virological Outcomes, and HIV Status Disclosure in Adolescents Living With Perinatally-Acquired HIV in the IeDEA-COHADO Cohort in Togo and Côte d'Ivoire, 2015-2017 - Marc Harris Dassi Tchoupa Revegue; Unoo Elom Takassi; François Tanoh Eboua; Sophie Desmonde; Ursula Belinda Amoussou-Bouah; Tchaa Abalo Bakai; Tchaa Abalo Bakai; Julie Jesson; Désiré Lucien Dahourou; Désiré Lucien Dahourou; Karen Malateste; Hortense Aka-; et al. (Frontiers Media S.A., 2021)
Background: Adolescents living with perinatally-acquired HIV (APHIV) face challenges including HIV serostatus disclosure. We assessed their 24-month outcomes in relation to the disclosure of their own HIV serostatus.Methods: Nested within the International epidemiologic Database to Evaluate AIDS pediatric West African prospective cohort (IeDEA pWADA), the COHADO cohort included antiretroviral (ART)-treated APHIV aged 10-19 years, enrolled in HIV care before the age of 10 years, in Abidjan (Côte d'Ivoire) and Lomé (Togo) in 2015. We measured the HIV serostatus disclosure at baseline and after 24 months and analyzed its association with a favorable combined 24-month outcome using logistic regression. The 24-month combined clinical immuno-virological outcome was defined as unfavorable when either death, loss to follow-up, progression to WHO-AIDS stage, a decrease of CD4 count >10% compared to baseline, or a detectable viral load (VL > 50 copies/mL) occurred at 24 months.Results: Overall, 209 APHIV were included (51.6% = Abidjan, 54.5% = females). At inclusion, the median CD4 cell count was 521/mm3 [IQR (281-757)]; 29.6% had a VL measurement, of whom, 3.2% were virologically suppressed. APHIV were younger in Lomé {median age: 12 years [interquartile range (IQR): 11-15]} compared to Abidjan [14 years (IQR: 12-15, p = 0.01)]. Full HIV-disclosure increased from 41.6% at inclusion to 74.1% after 24 months. After 24 months of follow-up, six (2.9%) died, eight (3.8%) were lost to follow-up, and four (1.9%) were transferred out. Overall, 73.7% did not progress to the WHO-AIDS stage, and 62.7% had a CD4 count above (±10%) of the baseline value (48.6% in Abidjan vs. 69.0% in Lomé, p < 0.001). Among the 83.7% with VL measurement, 48.8% were virologically suppressed (Abidjan: 45.4%, Lomé: 52.5%, p <0.01). The 24-month combined outcome was favorable for 45% (29.6% in Abidjan and 61.4% in Lomé, p < 0.01). Adjusted for baseline variables, the 24-month outcome was worse in Lomé in those who had been disclosed for >2 years compared to those who had not been disclosed to [aOR = 0.21, 95% CI (0.05-0.84), p = 0.03].Conclusions: The frequency of HIV-disclosure improved over time and differed across countries but remained low among West African APHIV. Overall, the 24-month outcomes were poor. Disclosure before the study was a marker of a poor 24-month outcome in Lomé. Context-specific responses are urgently needed to improve adolescent care and reach the UNAIDS 90% target of virological success.